2013
DOI: 10.1111/ecc.12047
|View full text |Cite
|
Sign up to set email alerts
|

Is a nurse-led telephone intervention a viable alternative to nurse-led home care and standard care for patients receiving oral capecitabine? Results from a large prospective audit in patients with colorectal cancer

Abstract: Home care nursing has been shown to be a valuable service for patients receiving oral chemotherapy; however, associated costs can be high and telephone-based services may be more cost-effective options. This prospective audit explored the usefulness of a nurse-led telephone intervention for supporting cancer patients treated with Capecitabine, comparing historical findings from a randomised trial evaluating a home-based intervention over standard care with a modified nurse-led telephone follow-up intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 18 publications
0
41
0
6
Order By: Relevance
“…Intervention timing varied according to the specific treatment being received. The vast majority were presented as supplementary to standard care (Cirillo et al., ; Cox et al., ; Delaney et al., ; Dixon, ; Hagopian & Rubenstein, ; Heidrich et al., ; Inman et al., ; Jefford et al., ; Jensen, Kristensen, Christensen, & Borre, ; Mordenti et al., ; Munro, Shaw, Clarke, Becker, & Greenwood, ; Sardell et al., ; Smithies et al., ; Young et al., , ; Zhang et al., ; Zheng et al., ), although four were described as standard care interventions (Archer et al., ; Craven, Hughes, Burton, Saunders, & Molassiotis, ; Hafiji et al., ; Kelly et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention timing varied according to the specific treatment being received. The vast majority were presented as supplementary to standard care (Cirillo et al., ; Cox et al., ; Delaney et al., ; Dixon, ; Hagopian & Rubenstein, ; Heidrich et al., ; Inman et al., ; Jefford et al., ; Jensen, Kristensen, Christensen, & Borre, ; Mordenti et al., ; Munro, Shaw, Clarke, Becker, & Greenwood, ; Sardell et al., ; Smithies et al., ; Young et al., , ; Zhang et al., ; Zheng et al., ), although four were described as standard care interventions (Archer et al., ; Craven, Hughes, Burton, Saunders, & Molassiotis, ; Hafiji et al., ; Kelly et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…High levels of overall satisfaction (Alter et al., ; Anderson, ; Badger et al., ; Beaver et al., ; Booker et al., ; , Cox et al., ; Craven et al., ; Garrett et al., ; Hafiji et al., ; Hagopian & Rubenstein, ; Hegel et al., ; Heidrich et al., ; Jensen et al., ; Kilbourn et al., ; Kimman, Bloebaum, et al., ; Leahy et al., ; Sardell et al., ; Steginga et al., ; Zhang et al., ) were reported; however, interpretation of these results should take into account the context of this assessment. Findings from low‐quality data and in some cases feedback were provided during the delivery of a telephone intervention (Anderson, ; Booker et al., ; Craven et al., ; Kelly et al, ), with potential for respondent and social desirability biases. Despite being a “comforting” indicator, overall satisfaction as a measure does not provide sufficient detail to enable key features of intervention design to be identified and maximised.…”
Section: Discussionmentioning
confidence: 99%
“…Toplam puanın yüksekliği araştırmanın metodolojik kalitesinin yüksekliğine işaret eder 23 HUHEMFAD-JOHUFON 2018, 5(3), 230-246 gruba ayrılmışlar. Telefon ile izlem yapılan grubun ilaç uyumu standart bakıma göre istatistiksel olarak anlamlı çıkarken (p<0.005) yan etki açısından anlamlı fark istatistiksel olarak önemsiz bulunmuştur(p>0,005) 20 . Spoelstra ve arkadaşlarının çalışmasında ise, danışmanlık verilen hasta grubunda, %95 oranında uygun ilaç kullanımı görülmüş olup gruplar arası fark istatistiksel olarak anlamlı (p<0.005) olarak değerlendirilmişidir 13 .…”
Section: Kalite Değerlendirmeunclassified
“…Four of these studies detailed successful outcomes of trialing telehealth support for medication and related symptoms, including a shared electronic care plan for professionals. 35,[155][156][157][158] Seven studies reported successful outcomes of telemonitoring. 106,[159][160][161][162][163][164] Mobile computing devices for information sharing, decision making, communication, and developing social capital were developed.…”
Section: Treatment-related (Five Studies)mentioning
confidence: 99%